Observing Grammatical Collocation in Students’ Writings - Beaty Novita Sari; Ingatan Gulö (Universitas Teknokrat Indonesia, 2019)
This research aimed to describe the types of grammatical collocation errors produced by English learners in their writings. The writers used a qualitative method for collecting and analyzing the data. The data were taken from first-year students’ essays. Collocations from fifteen essays were collected and analyzed. As the standard for the collocations being analyzed, The Oxford Collocation Dictionary and The BBI Combinatory Dictionary of English were used by the writers. The results showed that the students made grammatical collocation errors in their writings, with a total of 35 grammatical collocations. It was also found that verb-noun collocation is the most dominant error made, which indicated that the students faced difficulties in using proper verbs in collocations.Keywords: Collocation error, grammatical collocation, students’ writings